The green umbrella - Azúa Kramer, Jackie (North South, 2017)
When Elephant takes a quiet stroll with his green umbrella, he is hindered by Hedgehog, Cat, Bear, and Rabbit, each asserting that his umbrella is truly their boat, tent, flying machine, and cane.